Conduction recovery following pacemaker implantation after transcatheter aortic valve replacement. Issue 2 (4th January 2019) - Kaplan, Rachel M.; Yadlapati, Ajay; Cantey, Eric P.; Passman, Rod S.; Gajjar, Mark; Knight, Bradley P.; Sweis, Ranya; Ricciardi, Mark J.; Pham, Duc T.; Churyla, Andrei; Malaisrie, S. Chris; Davidson, Charles J.; et al.
Abstract: Background: Transcatheter aortic valve replacement (TAVR) is increasingly used to treat severe aortic stenosis. A frequent complication of TAVR is high‐grade or complete atrioventricular (AV) block requiring a permanent pacemaker (PPM). There are little data on the long‐term dependency on pacing after TAVR. The objective of this study was to determine the proportion of patients receiving a PPM for high‐grade or complete AV block after TAVR who remain dependent on the PPM in follow‐up and to determine any risk factors for, particularly the effect of postballoon dilation (PBD) on, pacemaker dependency. Methods: Of 594 consecutive patients without prior PPM undergoing TAVR (81.9% balloon‐expandable, 18.1% self‐expandable valve), 67 (13.1%) received a PPM after TAVR. PPM dependency was defined as AV block with a ventricular escape rate of ≤ 40 beats/min. Patient and procedural characteristics were examined according to PPM dependency status. Results: Of the 67 patients who received a PPM within 10 days after TAVR, 27/67 (40.3%) were dependent at first follow‐up and only 9/41 (21.9%) at 1 year. PPM dependency was more common after a self‐expanding valve (76.9% vs 31.5%, P < 0.01), in those who underwent PBD (66.7% vs 24.4%, P < 0.01), and in patients in persistent complete AV block at PPM implantation (62.5% vs 7.4%, P < 0.01). Conclusions: Fewer than half of patients who receive a new PPM following TAVR are pacemaker dependent at early follow‐up (< 30 days). The use of self‐expanding valves and PBD are associated with a markedly increased risk of PPM dependency.